ENHANCING VILLAGE-OWNED ENTERPRISES PERFORMANCE THROUGH EFFECTIVE GOVERNANCE: THE MEDIATING ROLE OF COMPETITIVE ADVANTAGE - Sigit Kurnianto; Dina Heriyati; Yanuar Nugroho; Lailatul Fiyatun Nikma (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2025)
This study aims to examine the effect of Governance (GV) on Organizational Performance (FP) with the mediation of Competitive Advantage (CA). The analysis method used is the SEM-PLS approach with SmartPLS 4 software. The primary data was collected through questionnaires with a Village-Owned Enterprises (BUM Desa) population in East Java, Indonesia. The sample used in the analysis was 80 BUM Desa managers. The results show that competitive advantage partially mediates the relationship between governance and BUM Desa performance. The implication of this study is the importance of improving governance to strengthen competitive advantage, which in turn will improve the organizational performance of BUM Desa. This research also provides insights for decision-makers to formulate more effective strategies for managing BUM Desa.